2018
DOI: 10.1186/s12974-018-1261-y
|View full text |Cite
|
Sign up to set email alerts
|

The plasticity of primary microglia and their multifaceted effects on endogenous neural stem cells in vitro and in vivo

Abstract: BackgroundMicroglia—the resident immune cells of the brain—are activated after brain lesions, e.g., cerebral ischemia, and polarize towards a classic “M1” pro-inflammatory or an alternative “M2” anti-inflammatory phenotype following characteristic temporo-spatial patterns, contributing either to secondary tissue damage or to regenerative responses. They closely interact with endogenous neural stem cells (NSCs) residing in distinct niches of the adult brain. The current study aimed at elucidating the dynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 70 publications
(89 reference statements)
8
66
1
Order By: Relevance
“…Astrocytes are the most abundant glia in the brain, and astrocytic activation also contributes to and expands the initial inflammatory response and neurodestructive effects of microglia [29,30]. Although initial studies on neuroinflammation suggested that microglial activation was detrimental to neurogenesis [31][32][33], more recent studies have proven the beneficial role of microglial activation on the regulation of the migration, proliferation, and differentiation of neural stem cells [34,35]. In particular, alternative activation of microglia (type M2) can increase neuroprotective factors such as nuclear factor erythroid 2-related factor 2 and heme oxygenase-1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are the most abundant glia in the brain, and astrocytic activation also contributes to and expands the initial inflammatory response and neurodestructive effects of microglia [29,30]. Although initial studies on neuroinflammation suggested that microglial activation was detrimental to neurogenesis [31][32][33], more recent studies have proven the beneficial role of microglial activation on the regulation of the migration, proliferation, and differentiation of neural stem cells [34,35]. In particular, alternative activation of microglia (type M2) can increase neuroprotective factors such as nuclear factor erythroid 2-related factor 2 and heme oxygenase-1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the microglia can also play a negative role, through secretion of damaging proinflammatory cytokines which increase inflammation in the area of healthy cells [5,17]. We consider the damage D caused by the activated microglia to represent secondary damage in the case of stroke [2,14]. The following differential equation describes this damage:…”
Section: Modelling Of the Effect Of Microglia On The Brain In A Strokmentioning
confidence: 99%
“…The harmful effects, which are toxic to tissues, occur primarily through the production of free radicals [12,13]. This reaction is important in removing damaged cells from the brain tissue; however, it can also increase the harm to brain cells by producing free radicals that are toxic to healthy cells [2,14,15]. There has been an increasing amount of evidence suggesting that ischemic inflammation may be vital to the issue of pathogens, as ischemic stroke results not only in damage and neuronal loss but also in sustained neuroinflammation after stroke [3,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As major immune-competent cells in the brain, microglia exert multiple functions under various physiological and pathological conditions (Wolf, Boddeke, & Kettenmann, 2017). Notably, recent studies have demonstrated that microglia regulate proliferation and differentiation of NSCs and OPCs either positively or negatively depending on conditions, thereby affecting the cellular dynamics of the postnatal brain in both the VZ-SVZ and DG (Kreisel, Wolf, Keshet, & Licht, 2018;Morton, Neckles, Seluzicki, Holmberg, & Feliciano, 2018;Naruse, Shibasaki, Shimauchi-Ohtaki, & Ishizaki, 2018;Vay et al, 2018;Walton et al, 2006). Yet, what impact microglia have on normal brain development remains to be further investigated.…”
Section: Box 1 Impacts Of Non-neuronal/glial Cell Types On Postnatal mentioning
confidence: 99%